Bile secretion in the chicken: effects of secretin, cholecystokinin- pancreozymin and duodenal mucosal extract (Revista Española de Fisiología, 1986)
The effects of i.v.administration of secretin, CCK-PZ, acid extracts from the duodenal mucosa and the duodenal acidification of the intestine on bile secretion were studied in anaesthetized chickens.Secretin and acid extracts from the duodenal mucosa, which increase bile flow, caused comparable modifications in bile composition; infusion of HCl to the duodenum only induced slight modifications.CCK-PZ caused a pronounced cholecystokinetic effect and, to a lesser degree, it also showed choleretic effects.The results suggest that in the hormonal regulation of bile secretion in the chicken CCK-PZ is more important than secretin and furthermore that the choleretic activity of the latter must be carried out by other secretin-like peptides.